Gastrin and Nitric Oxide Production in Cultured Gastric Antral Mucosa Are Altered in Response to a Gastric Digest of a Dietary Supplement - MacNicol, Jennifer L.; Pearson, Wendy (Frontiers in Veterinary Science, 2021)
In vitro organ culture can provide insight into isolated mucosal responses to particular environmental stimuli. The objective of the present study was to investigate the impact of a prolonged culturing time as well as the addition of acidic gastric fluid into the in vitro environment of cultured gastric antral tissue to evaluate how altering the commonly used neutral environment impacted tissue. Furthermore, we aimed to investigate the impact of G’s Formula, a dietary supplement for horses, on the secretion of gastrin, interleukin1-beta (IL-1β), and nitric oxide (NO). These biomarkers are of interest due to their effects on gastric motility and mucosal activity. Gastric mucosal tissue explants from porcine stomachs were cultured in the presence of a simulated gastric fluid (BL, n=14), simulated gastric fluid containing the dietary supplement G’s Formula (DF, n=12), or an equal volume of phosphate buffered saline (CO, n=14). At 48 and 60h 10-5M carbachol was used to stimulate gastrin secretion. Cell viability was assessed at 72h using calcien and ethidium-homodimer 1 staining. Media was analyzed for gastrin, IL-1β, and NO at 48, 60 and 72h. There were no effects of treatment or carbachol stimulation on explant cell viability. Carbachol resulted in a significant increase in gastrin concentration in CO and DF treatments, but not in BL. Nitric oxide was higher in CO than BL, and NO increased in the CO and DF treatments but not in BL. In conclusion, the addition of carbachol and gastric digests to culture media did not impact cell viability. The use of an acidic gastric digest (BL) reduced the effect of cholinergic stimulation with carbachol at a concentration of 10-5M and reduced NO secretion. The addition of the dietary supplement to the gastric digest (DF) appeared to mediate these effects within this model. Further research is required to evaluate the specific effects of this dietary supplement on direct markers of mucosal activity and the functional relevance of these results in vivo.